Place and provision of palliative care for children with progressive cancer: a study by the Paediatric Oncology Nurses' Forum/United Kingdom Children's Cancer Study Group Palliative Care Working Group. - Vickers, J; Thompson, A; Collins, G; Childs, M; Hain, R (2007)
PURPOSE: The purpose of this study was to describe and show effectiveness of the outreach team model of palliative care (PC) in allowing home death for children with incurable cancer. PATIENTS AND METHODS: Over 7 months, 185 children from 22 United Kingdom oncology centers were recruited to a prospective questionnaire survey. RESULTS: One hundred sixty-four children from 22 centers died (median age, 8.7 years; 88 boys, 76 girls). One hundred twenty-six families completed two or more questionnaires. One hundred twenty (77%) of 155 with complete data died at home. Preference for home death was recorded in 90 (68%) of 164 and 132 (80%) 164 at study entry and last month of life, respectively. Death occurred in preferred place for 84 (80%) of 105 with recorded preference at entry. Forty-one (25%) of 164 and 68 (41.5%) of 164 needed no outpatient or inpatient hospital visits, respectively. A named individual provided on-call PC advice by phone or home visit in 22 (100%) and 18 (82%) of 22 oncology centers, respectively. As PC progressed, involvement of oncologist and social worker appeared less, whereas pediatric oncology outreach nurse specialists (POONSs) remained prominent. CONCLUSION: Preference for home death expressed by families in our study is similar to others, but the proportion of children actually able to die there is higher. Home death is facilitated by this model. Key components are POONSs, pediatric palliative and/or oncology specialist, and general practitioner. Professional roles change during PC and after death. An ongoing role for the oncology team in bereavement support is highlighted.